Investigation of Waltheria indica L. (sleepy morning plant) as pathogen killing agent from shallow well water revealed a potential alternative for water disinfection - Josephat Ilunde; Nelson Mpumi; Mwema Felix Mwema; Revocatus L. Machunda (PLoS ONE, 2025)
In many parts of the world, shallow well drinking water is contaminated and often consumed without treatment, contributing to over 3.4 million deaths annually due to water-related diseases. This research aims to assess the efficacy of Waltheria indica plant root extracts as an affordable method for disinfecting shallow well water in rural Tanzania. Laboratory experiments were conducted using dried plant roots in powdered form, as well as soaked and boiled extracts, to test their effectiveness in eliminating Escherichia coli and total coliforms at varying concentrations and contact times. Contaminated water samples were collected from shallow wells in the Misungwi district, Tanzania, and treated using all three forms of Waltheria indica extracts. Phytochemical profiling of the plant root extracts was performed using Liquid Chromatography tandem Mass Spectrometry (LC-MS/MS) to identify potential antimicrobial compounds. The disinfection efficacy was evaluated using a flocculator with 1-litre beakers to determine bacterial removal and the effects on key physicochemical parameters. Results showed that all three extract forms significantly reduced E. coli and total coliforms, achieving up to 100% reduction within 12 hours. The soaked extract was most effective, reducing E. coli and total coliforms by approximately 94.3% and 93.8%, respectively, followed by the boiled extract (83.9% and 85.8%) and the powdered form (81.9% and 68.2%). The treated water’s pH and total dissolved solids (TDS) were not significantly affected across all treatments. However, turbidity levels remained above the acceptable limit of 5 NTU, indicating the need for further optimization. Overall, the results suggest that Waltheria indica plant root extracts have strong potential as a natural, low-cost water disinfectant.